Histopathological and Immunohistochemical Studies of Cowpox Virus Replication in a Three-Dimensional Skin Model. Issue 1 (July 2016) - Tamošiūnaitė, A.; Hoffmann, D.; Franke, A.; Schluckebier, J.; Tauscher, K.; Tischer, B.K.; Beer, M.; Klopfleisch, R.; Osterrieder, N.
Summary: Human cowpox virus (CPXV) infections are rare, but can result in severe and sometimes fatal outcomes. The majority of recent cases were traced back to contacts with infected domestic cats or pet rats. The aim of the present study was to evaluate a three-dimensional (3D) skin model as a possible replacement for animal experiments. We monitored CPXV lesion formation, viral gene expression and cell cycle patterns after infection of 3D skin cultures with two CPXV strains of different pathogenic potential: a recent pet rat isolate (RatPox09) and the reference Brighton red strain. Infected 3D skin cultures exhibited histological alterations that were similar to those of mammal skin infections, but there were no differences in gene expression patterns and tissue damage between the two CPXV strains in the model system. In conclusion, 3D skin cultures reflect the development of pox lesions in the skin very well, but seem not to allow differentiation between more or less virulent virus strains, a distinction that is made possible by experimental infection in suitable animal models.